Transmisiones y tendencias deportivas en la convergencia digital - Cornejo Silva, Carlos Humberto (2024)
The present research paper sought the impact of the influence of sports broadcasts through a classification of tuning according to ages in the audience, evaluating the power of digital platforms. Through a descriptive-exploratory, nontransactional design and with a mixed qualitative-quantitative approach, with research instruments based on questionnaire and survey, based on a sample not stratified for convenience. Its analysis was based on descriptive statistics techniques and synthesis of an interview with an expert in the field. Theoretical principles were established that showed the evolution of traditional media, in particular radio, and its transition to the digital medium. As for the results, the population was segmented in 19.20% between the age range of 19-25 years and over 50 years with about 27.8% of the total, and the third section was 31-35 years with a percentage of 15.20%, demonstrating that consumption preferences are between these 3 age ranges. Demonstrating that Youtube is the platform chosen by the users consulted as the predominant one with 47.68%. Finally, it was noted that traditional media have a representation of only 33.11% of the 66.89% of digital media, even though they must adapt to digital formats in order not to disappear.